Analysis of flow field design on vanadium redox flow battery performance: Development of 3D computational fluid dynamic model and experimental validation. (15th October 2018) - Messaggi, M.; Canzi, P.; Mereu, R.; Baricci, A.; Inzoli, F.; Casalegno, A.; Zago, M.
Highlights: A model coupling fluid dynamics and electrochemistry of a VRFB is developed. 3D simulations are performed for 25 cm 2 interdigitated and serpentine flow fields. Serpentine flow field allows better performances with higher auxiliary consumption. Interdigitated flow field shows reduced heterogeneity and reduced pressure drops. Under-the-rib fluxes play a crucial role in determining performance and heterogeneity. Abstract: Homogeneous distribution of the electrolyte over the porous electrode is a critical issue hindering the commercialization of vanadium redox flow batteries, owing to increased overpotential at high current and limited power density of the system. Therefore, an understanding of the physical phenomena regulating mass transport of the electrolyte is crucial to improving system performance. The present work describes the development and experimental validation of a 3D computational fluid dynamic model of a vanadium redox flow battery in a half-cell configuration with an active area of 25 cm 2 . The model simulates the influence of a single serpentine and an interdigitated flow field. The adoption of the half-cell configuration allows the negative electrode to be considered as a pseudo-reference electrode with zero potential loss, leading to a reduction in computation time and the number of fitting parameters, which can be determined with reduced uncertainty. The developed model includes a traditional fluid dynamic analysis of the electrolyte in the flow field and in the porous electrode, coupled with the electrochemistry of the reactions involved. In both the experiments and the simulations, the single serpentine distributor exhibits better performance and higher pressure drops compared to those of the interdigitated geometry under all the investigated operating conditions. In the analysis of the local reaction rate, both distributors experienced increased reaction rates under the rib, induced by a by-pass flow between adjacent channels. The reaction rate shows a highly heterogeneous distribution in the serpentine geometry, while it is more uniform in the interdigitated configuration.